Inserción laboral femenina y contribución familiar en el programa trabaja Perú distrito de Punchana provincia de Maynas 2021 - López Perea, Jheam Carlos (2023)
The main objective of this study was to determine the relationship between female labor insertion and family contribution in the Trabaja Peru Program of the Punchana district, 2021, opting for applied research under a descriptive correlational level and non-experimental design, a sample of 47 women was taken, being surveyed through the questionnaire, obtaining the following results, female labor insertion is regular (24%), because the program almost never generates temporary employment in areas of poverty and extreme poverty, sometimes offers quality work through local projects, however, they have never received training, they also consider that they are almost never in accordance with the contract modality, the salary received sometimes rewards their ability to work and that their current job almost never maintains a pleasant environment to carry out their activities. Likewise, the variable family contribution in the Trabaja Peru Program is regular (28%), since having a job has almost never allowed him to have greater purchasing power, but sometimes it has made it easier for his family to acquire goods and services, likewise, sometimes he has managed to participate in the family economic income, having a job has almost never allowed him to offer his family better conditions to live, but sometimes he has been able to acquire work experience to support his family, rarely has greater participation in the head of the household. Finally, it was concluded that there is a significant relationship between female labor insertion and family contribution in the Trabaja Peru Program, Punchana district, Maynas 2021 province, with the positive coefficient being considerable (r = 0.845).